Servant Leadership and Life Satisfaction at Public School in Indonesia: Career Satisfaction as Mediator - Dami, Zummy Anselmus; Imron, Ali; Burhanuddin, Burhanuddin; Supriyanto, Achmad; Mustiningsih, Mustiningsih (Pedagogika, 2023)
The research aimed to test servant leadership role in improving life satisfaction through career satisfaction. The method used was quantitative with structural equation modeling. The results showed that servant leadership has a positive and significant effect on career and life satisfaction, career satisfaction has a positive and significant influence on life satisfaction, and career satisfaction was a complementary mediator between servant leadership and teacher life satisfaction.